Prototipe Aplikasi Bimbingan Tugas Akhir Mahasiswa Berbasis Web - Meliana Christianti Johan; Erico Darmawan Handoyo; Sulaeman Santoso (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Final Project is generally regarded as mandatory for university students to graduate. This holds true in the Faculty of Information Technology in Maranatha Christian University Bandung, Indonesia. As a continuation of previous research which discusses the process of submitting student final project topics, this research will focus on documenting requests for final project guidance. In the final project process, after a student submits a final assignment topic and the topic is accepted to be worked on as a final assignment, students must then carry out the guidance process with their final assignment supervisor. This process includes the student requesting an audience with the aforementioned supervisor. This process holds several problems, one of which is that the content of the discussion between the supervisor and the student tends to be lost or misunderstood. This research will assist the process of supervising student final assignments so that students can apply for guidance with supervisors through this application and lecturers can confirm the content of the discussion for the student. This application is a web-based application so it can be used anytime and anywhere.